Habituelle Urbanität - Dirksmeier, Peter (ERDKUNDE, 2006)
As the starting point for the development of society, cities are characterised by a high degree of individualisation and the anonymity of their inhabitants. Anonymity, or constant contact with strangers, offers individuals a greater scope of action. Urbanity can therefore be defined as the contingency of a city, which manifests itself in the greater scope for action of its inhabitants compared to other forms of settlement. This essay introduces the concept that the habitus of city dwellers is instrumental in helping them cope with the additional risks and opportunities offered by the city. It develops the theory that this incorporation of the conditions in the city occurs with the help of a kind of capital which, in the following, is derived from the social theory of PIERRE BOURDIEU. On the basis of the term habitual urbanity, largely recognised but still inadequately researched transformational processes in rural regions can then be theoretically investigated.